Simulating the future of the Swedish baby-boom generations - N. Anders Klevmarken; Kristian Bolin; Matias Eklöf; Lennart Flood; Urban Fransson; Daniel Hallberg; Sören Höjgård; Björn Lindgren; Andrea Mitrut; Mårten Lagergren (Uppsala University, Department of Economics, 2007)
For the purpose of studying the consequences of the ageing of the Swedish population a group of scientists have enlarged the microsimulation model SESIM - originally developed at the Swedish Ministry of Finance - with modules that simulate health status, take up of sickness benefits, retirement, the utilization of health care and social care and the dynamics of the income and wealth distributions. This paper motivates and reviews the structure of these modules with a focus on problems and solutions. It also summarizes the main results of the simulations. A complete description of the models and results are forthcoming in a volume included in the Elsevier series Contributions to Economic Analysis.
urn:nbn:se:uu:diva-11648
Keywords: C15; C50; D10; D31; H24; H31; H55; I12; I32; J10; J22; J26; R21; R23; 330; Microsimulation; Ageing; Retirement; Health status; Health care; Social care; Distribution of Income; Distribution of Wealth; Poverty; Alternde Bevölkerung; Gesundheit; Einkommensverteilung; Soziale Sicherung; Simulation; Schweden